COMPARISON OF PASSIVE SENTENCES IN ENGLISH AND INDONESIAN - Retno Fentari (Jurnal Ilmiah AZZIQRI: Kajian Keislaman dan Kependidikan, 2022)
The difficulty of a teacher teaching a second language to students can be overcome by contrastive analysis, where it is assumed that learning a second language is influenced by mastery of the first language. The purpose of this article is to describe the level of comparison of Indonesian and English passive sentences which can provide benefits as a reference in teaching English as a second language. The research was conducted using a qualitative method, with reference to literature from Indonesian and English sources.Passive sentences in Indonesian seen from their structure use "di-", "ter-" or "to-". Meanwhile, English only knows "to be + past participle" which depends on the time of occurrence (according to the tenses). The context of the sentence must be considered so that the meaning contained in it can really be understood. After analyzing and looking for equivalents and comparisons in passive sentences in Indonesian and English, the writer has found the similarities and differences that exist. Both the similarities and differences can be seen structurally and pragmatically.